The verb in a Czech sentence: How do foreign learners of the Czech language perceive the structure of a Czech sentence? - Koudelíková, Tereza (Bohemistyka, 2023)
The aim of this paper is to illustrate through two sentences how foreign learners perceive the structure of the Czech language. Respondents were asked to write answers on how the language works, what the syntactic relations of the sentence members are, and why the chosen words have their concrete forms with respect to the whole clause. The survey collected answers of a wide range of respondents with respect to both the number of years of studying the Czech language and their native language. After a brief introduction to the Czech language focusing mainly on the syntactic and morphological properties that were at the center of attention in this survey, the chosen survey questions are analyzed. It turned out that learners of the Czech language were willing to participate in this survey; in total the respondents provided answers in 95.7 % of cases, which helped to get more exact results. It emerged that respondents of the survey fully answered the questions correctly in 52.7 % of cases. The remaining 47.3 % of responses were either wrong or incomplete depending on the form of the question. The results of this survey lead us to the conclusion that it might be worth focusing more on the system of morphology and syntax while teaching Czech for foreigners. The complete list of answers with respect to the number of years of studying the Czech language is attached in the appendix.